EVALUASI IMPLEMENTASI DANA BOK DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KOTA BIMA TAHUN 2015 - Aris Iwansyah; Julita Hendrartini; Muhamad Faozi Kurniawan (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2019)
Background: Health Operational Cost (Bantuan Operasional Kesehatan/BOK) is government aids for local government to accelerating achievement of national priority programs, especially health aspect in Millennium Development Goal’s (MDG), through improvement performances of Public Health Centers (PHC) and the networks. Funding of Health Operational Cost to support PHC on providing promotive and preventive programs to community due to PHC services in district are likely to be directed on curative measures. Funding allocation of Health Operational Cost has been decreasing in Bima from IDR.1.412.500.000 on 2014 became IDR.521.464.000 on 2015. Therefore, evaluation of program implemetation by funding of Health Operational Cost on 2015 in Bima are needed to be examined. Objective: To find out the achievement implemetation of Health Operational Cost program in Public Health Center under District Health Office in Bima at 2015. Methods: The study design was qualitative and quantitative using descriptive case study. Tehnique of sample selection by using purposive sampling. Data analysis was conducted by descriptive qualitative. Results: Decreasing allocation funding of Health Operational Cost affected to planning and implementation of program, while Health Operational Cost became main sources of fund to external program in PHC due to lack of financial support from Regional government budget. Health Operational Cost have not been able to support achievement of Minimas Services Standar in Bima. Many head of PHC still less understanding to technical guide of Health Operational Cost so affected on decision-making of program and lack of monitoring and evaluation by District Health Department. Conclusion: The implementation of BOK program in Bima City is not the best enough especially in supporting SPM target in 2015.